The Law on Presumption in Corruption Cases in Malaysia - Abdul Rahman, Rohana (Philippine Association of Institutions for Research, 2015)
From a legal perspective, bribery and corruption cases can be unduly complicated and difficult to prove because there is no real victim. The briber and recipient of gratification somehow gain benefit from their corrupt transaction with each other. In many corruption cases, more often than not the prosecution faces hostile or uncooperative witnesses who refuse to assist the prosecution in such cases. To reduce the complexity of proving that any advantage was given corruptly, the law on presumption of corruption has been incorporated in the old Prevention of Corruption Act 1961, and later in Anti-Corruption Act 1997 and currently the Malaysian Anti Corruption Commission Act 2009. There has been mixed reaction from the prosecution and defense lawyers in respect of the law on a presumption of corruption in bribery and corruption cases. This paper seeks to highlight the application of a presumption of corruption in certain circumstances as provided in the statute, the right to defend on balance of probability and whether such presumption is contrary to human rights. The paper argues once statutory presumption of corruption is invoked, it can be challenging to rebut and the burden of proof must remain on the prosecution to prove their case beyond reasonable doubt. The paper stresses that presumption of corruption is rebuttable if the accused is able to discharge his burden of proving on a balance of probabilities that his receipt of the same was not a gratification